Effect Of Financial Performance On Stock Price In The Telecommunications Sector Listed On The Indonesian Stock Exchange For The 2018-2022: - Fauziah, Alvi; Rahwana, Kusuma Agdhi; Wibawa, Gian Riksa (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The aim of this research is to find out the partial and simultaneous influence of these variables on share prices in telecommunications companies. The data used uses secondary data. The analytical tool used in this research is panel data regression using eviews 12. The results of the t test research show that Return On Assets does not have a significant effect on stock prices in the Telecommunications sector listed on the BEI for the 2018-2022 period. The results of the t test research show that Earning Per Share has no significant effect on share prices in the Telecommunications sector listed on the IDX for the 2018-2022 period. The results of the F test research show that Return On Assets and Earning Per Share simultaneously have a significant effect on share prices in the telecommunications sector listed on the IDX for the 2018-2022 period.